How did Teachers and Students Experience a Hybrid Learning model in Costa Rian Higher Education? - Chavarría Vargas, Aleida (2026)
While much attention has been focused on hybrid learning studies in Higher Education, teachers and students continue playing a crucial role in teaching and learning outcomes. This article presents a study on the experiences of students and teachers in the implementation of a hybrid learning model in higher education. A qualitative method was used, including focus groups with students, who were selected voluntarily or based on accessibility, and interviews with teachers from the same faculty. These participants provided feedback on their experiences with face-to-face and virtual learning, as well as suggestions for improvement. A total of 107 students participated in the focus groups, and 7 teachers were interviewed, representing Law, English Teaching and Early Childhood Education programs from a university in Costa Rica. The findings reveal that participants expressed satisfaction with the model due to its flexibility in attending classes either in person or virtually. They also reported positive outcomes related to recorded lessons as pedagogical support, innovation and development of interactive strategies facilitating the acquisition of new skills among students. The implemented model positively impacted retention rated by providing flexibility and underscored the importance of teachers’ adjustments to promote dynamic and active learning. However, clear opportunities for improvement were identified, including course scheduling to avoid conflicts with other courses, workload management, improve UbD´s backward design process, low participation in discussions, and lack of effective feedback from teachers.